Notes to lichen-forming and lichenicolous fungi in Ukraine IV (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Materials and methods: field observations and herbarium collections, microscope technique. Nomenclature: Index Fungorum. Results: In this contribution, new data concerning lichen-forming and lichenicolous fungi in Ukraine are presented. It includes new record and confirmations to the Ukrainian administrative regions of 62 species of lichen-forming and 14 species of lichenicolous fungi in the genera of Abrothallus, Alyxoria, Anisomeridium, Arthonia, Arthopyrenia, Athallia, Athelia, Aspicilia, Bacidia, Bactrospora, Calogaya, Caloplaca, Catillaria, Celothelium, Chaenotheca, Didymocyrtis, Diplotomma, Diploschistes, Enchylium, Eopyrenula, Erythricium, Flavoplaca, Graphis, Heterocephalacria, Illosporiopsis, Kuettlingeria, Laetisaria, Lahmia, Lecania, Lecanora, Lepraria, Lichenoconium, Lichenostigma, Lichenothelia, Lobothallia, Montanelia, Peltigera, Pertusaria, Physcia, Physconia, Placidium, Placynthiella, Polyozosia, Pronectria, Protothelenella, Pterygiopsis, Punctelia, Ramalina, Rinodina, Scoliciosporum, Strangospora, Taeniolella, Talpapellis, Thelenella, Xylopsora, Verruculopsis and Verrucaria. Among them 22 species are the first time reported to the Cherkasy region, 18 species new to the Kirovograd region, 13 species new to the Donetsk region, 11 species new to the Ivano-Frankivsk region, 5 species new to the Vinnytsa region, 4 species new to the Kharkiv region, 3 species new to the Ternopil region, two species new to the Sumy and Zhytomyr regions, one species new to the Chernivtsi, Kherson, Kyiv, Poltava and Rivne regions. The paper includes recent records of lichens and lichenicolous fungi from National Nature Parks of Ukraine: Buzkyi Gard, Carpathian, Holosiivsky, Homilshanski Lisy, Kholodnyi Yar, Svyati Gory as well as Kreidova Flora and Kaniv Nature Reserves and Velykoburlutskyi Steppe Regional Landscape Park.
Keywords: biodiversity, new records, Calicium, Montanelia, Protothelenella, Pterygiopsis, Punctelia